Bardet-Biedl syndrome caused by compound heterozygosity in BBS12 gene: a case report of one family with three affected members - Simičić Majce, Ana; Tudor, Darija; Simunovic, Marko; Todorovic, Marko; Parlov, Mladenka; Lozic, Bernarda; Saraga-Babić, Mirna; Saraga, Marijan; Arapović, Adela (Frontiers in Pediatrics, 2023)
Introduction: Bardet-Biedl syndrome (BBS) is a rare genetic syndrome caused by a mutation in one of 26 different genes responsible for normal structure and/or function of primary cilia. The syndrome is characterized by multiorgan involvement with gradual onset of occurrence of clinical signs and symptoms resulting in great phenotypic variability and what is more important, often difficulties with establishing the timely diagnosis.Case report: we report a case of a one family with three members with BBS caused by a very rare mutation, a compound heterozygosity in BB12 gene. Even though all three patients have the same type of mutation, they express a significant diversity in clinical expression as well as renal impairment.Conclusion: this is a case report of a rare clinical syndrome caused by a very rare genetic mutation and it emphasizes the importance of genetic analysis in the timely diagnosis of oligosymptomatic patients with BBS, in order to possibly prevent long-term complications.